2010
DOI: 10.1242/jcs.073346
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine fibronectin directs matrix assembly and crosstalk between cell–matrix and cell–cell adhesion in vascular endothelial cells

Abstract: SummaryCellular fibronectin (cFN) variants harboring extra FN type 3 repeats, namely extra domains B and A, are major constituents of the extracellular matrix around newly forming blood vessels during development and angiogenesis. Their expression is induced by angiogenic stimuli and their assembly into fibrillar arrays is driven by cell-generated tension at 51 integrin-based adhesions. Here, we examined the role and functional redundancy of cFN variants in cultured endothelial cells by isoform-selective RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 78 publications
(77 reference statements)
12
71
0
Order By: Relevance
“…The requirement for polymerized versus protomeric fibronectin in the angiogenic process is not understood, but the finding suggests that the polymerizing fibronectin fibrils provide important angiogenic cues that are not found in protomeric fibronectin. This concept is supported by accumulating evidence indicating that fibronectin, its isoforms, its polymerization and its secondary structure all impact on neovascularization, indicative of an essential role for topographical organization of the fibronectin matrix in endothelial cell biology (Cseh et al, 2010;Le Saux et al, 2011;Mitsi et al, 2006;Uemura et al, 2006). In the present study, we show that anastellin, a homophilic binding peptide of fibronectin, drives conformational changes within the assembled fibronectin matrix that influence the endothelial microvessel cell response to angiogenic growth factors.…”
Section: Discussionsupporting
confidence: 67%
“…The requirement for polymerized versus protomeric fibronectin in the angiogenic process is not understood, but the finding suggests that the polymerizing fibronectin fibrils provide important angiogenic cues that are not found in protomeric fibronectin. This concept is supported by accumulating evidence indicating that fibronectin, its isoforms, its polymerization and its secondary structure all impact on neovascularization, indicative of an essential role for topographical organization of the fibronectin matrix in endothelial cell biology (Cseh et al, 2010;Le Saux et al, 2011;Mitsi et al, 2006;Uemura et al, 2006). In the present study, we show that anastellin, a homophilic binding peptide of fibronectin, drives conformational changes within the assembled fibronectin matrix that influence the endothelial microvessel cell response to angiogenic growth factors.…”
Section: Discussionsupporting
confidence: 67%
“…However, recent in vivo studies suggest that in addition to paracrine functions (Yoshino et al, 2014), Fn1 could also signal in a cell-autonomous manner (Cseh et al, 2010;Liu et al, 2010;Serres et al, 2014;Stenzel et al, 2011). By using genetic and cell biological approaches, the studies reported in this paper are the first to demonstrate the requisite, cell-autonomous role of Fn1 in the regulation of cardiovascular development.…”
Section: Role Of Fn1 and Integrin α5 In Nc Development And Cardiovascmentioning
confidence: 81%
“…37 In the absence of subendothelial FN matrix, endothelial cells are thought to undergo a switch from ␣ 5 ␤ 1 to ␣ v ␤ 3 integrin-based adhesion, associated with a disruption of adherens junctions. 38 In turn, ␣ v ␤ 3 engagement promotes angiogenesis, in part via interaction with VEGF receptor 2. 39 Thus, FN cleavage by extracellular calpains would promote angiogenesis by both generating proangiogenic fragments and limiting FN adhesive functions.…”
Section: Discussionmentioning
confidence: 99%